Embodied Love: Cognitive Poetics and the Somatic Imagery in E. E. Cummings’ Love Poetry - Hemad, Atyaf Abdulrazzaq (NIU Journal of Humanities, 2026)
The data of this research project provides an in-depth study of cognitive poetics and the mechanisms of somatic imagery and embodied love in the lyrical oeuvre of E. E. Cummings. This love poetry is historically denied by the early formalist critics either of being sentimentally conventional or just typographical eccentricities, but is here reinstated as an extremely refined phenomenological place of abstract emotional experiences made concrete through visceral body experiences. This study is based on a combination of three theories: Conceptual Metaphor Theory (CMT), Image Schema theory, and cognitive blending, and examines how Cummings evades Cartesian dualism to develop an ontology of love that is based on biological and physical reality. The cognitive frames in which linguistic disorientation calls readers to experience love as a spatial, embodied and tactile phenomenon are traced in a careful textual analysis based on canonical texts such as "somewhere i have never travelled, gladly beyond," "i carry your heart with me (i carry it in," and "love is thicker than forget. Cummings' typographic or syntactic aberration, the paper posits, is not simply a form of aesthetic novelty, but rather a means to conceptualize his emotionally intimate experience and one that mirrors emotional proximity. In sum, this study situates Cummings as a major player among the linguistic embodiment folks, showing that in his poetic cosmos love is not a mental state or a thing, but something that is impossible to escape, that is constantly happening, in the body.